3-D stress intensity factors due to full autofrettage for inner radial or coplanar crack arrays and ring cracks in a spherical pressure vessel. (April 2015) - Perl, M.; Steiner, M.
Highlights: SIFs for radial and coplanar crack arrays, and ring cracks in a spherical vessel. Effect of the number of cracks/crack density on the SIFs in radial/coplanar arrays. The influence of crack ellipticity and depth, and the vessel's geometry on the SIFs. The importance of the autofrettage model employed including the Bauschinger effect. Comparison between arrays of coplanar cracks and a ring crack. Abstract: Three dimensional, stress intensity factor for inner radial or coplanar crack arrays and ring cracks prevailing in an autofrettaged spherical pressure vessel are evaluated. The 3-D analysis is performed via the finite element method implementing a novel realistic autofrettage residual stress field incorporating the Bauschinger effect. SIFs are evaluated for arrays of radial or coplanar cracks and ring cracks of depth to wall thickness ratios of a / t  = 0.1–0.6, and ellipticities of a / c  = 0.2–1.0 in fully autofrettaged spherical vessels, ε  = 100%, of R o / R i = 1.1, 1.2, and 1.7. SIFs are evaluated for radial arrays containing n  = 1–20 cracks, and for arrays of coplanar cracks of δ  = 0–0.95 densities.